2018
DOI: 10.1016/j.ajhg.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polygenic Risk Scores for Multiple Cancers in a Phenome-wide Study: Results from The Michigan Genomics Initiative

Abstract: Health systems are stewards of patient electronic health record (EHR) data with extraordinarily rich depth and breadth, reflecting thousands of diagnoses and exposures. Measures of genomic variation integrated with EHRs offer a potential strategy to accurately stratify patients for risk profiling and discover new relationships between diagnoses and genomes. The objective of this study was to evaluate whether polygenic risk scores (PRS) for common cancers are associated with multiple phenotypes in a phenome-wid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
110
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 160 publications
(113 citation statements)
references
References 52 publications
1
110
0
2
Order By: Relevance
“…A common study design involves phenotype-specific case-control sampling, where all observed cases for a particular phenotype are selected and some subset of (possibly matched) controls for that phenotype are sampled from the biobank. 10,87 Cases are often defined as subjects receiving a particular diagnosis code a prespecified number of times, for example, twice. An advantage of case-control sampling is that it does not require additional longitudinal information and instead relies on dichotomized phenotypes, but it is heavily dependent on the "case" and "control" definitions.…”
Section: Defining the Study Samplementioning
confidence: 99%
See 3 more Smart Citations
“…A common study design involves phenotype-specific case-control sampling, where all observed cases for a particular phenotype are selected and some subset of (possibly matched) controls for that phenotype are sampled from the biobank. 10,87 Cases are often defined as subjects receiving a particular diagnosis code a prespecified number of times, for example, twice. An advantage of case-control sampling is that it does not require additional longitudinal information and instead relies on dichotomized phenotypes, but it is heavily dependent on the "case" and "control" definitions.…”
Section: Defining the Study Samplementioning
confidence: 99%
“…The software KING (Kinship-based Inference for GWAS) uses genotype data to determine pairwise kinship between patients. 107 We might then define the study sample restricted to unrelated patients and apply methods that rely on independence between patients (eg, Firth-corrected logistic regression in Fritsche et al 10 ). Statistical modeling approaches such as mixed modeling (eg, SAIGE) can also be used to account for residual correlations between individuals.…”
Section: Defining the Study Samplementioning
confidence: 99%
See 2 more Smart Citations
“…We applied Meta-MultiSKAT to meta-analyze four white blood cell (WBC) subtype traits from the Michigan Genomics Initiative (MGI; Fritsche et al, 2018) study and the SardiNIA study (Sidore et al, 2015;Vacca et al, 2006). In addition to detecting the genes PRG2 [MIM: 605601] and RP11-872D17.8, that had significant association signals with WBCs within one of the studies, Meta-MultiSKAT further identified two additionally associated genes (IRF8 [MIM: 601565] and CCL24 [MIM: 602495]) that did not have any significant signals in either of the studies but were identified as significant only as a result of meta-analysis.…”
Section: Introductionmentioning
confidence: 99%